The use of hedges by Malay writers: a study on the discussion section of theses in English language and applied linguistics - Yasin, Nik Nadiah Amalina; Pilus, Zahariah; Abu Bakar, Shazna (2016)
The present study examines the use of lexical hedges by 25 Malay writers in the discussion section of their Masters theses in English Language Studies, Applied Linguistics and English as a Second Language. The lexical hedges used by the writers were categorized into types which were determined based on the taxonomy of hedges proposed by Hyland (2000). The types of lexical hedges used were then compared to those used by native English writers. The study found that the Malay writers used all types of lexical hedges examined. The study also found some noticeable differences between native and non-native writings in terms of hedging tendencies. Findings from this study can be useful for English language practitioners particularly those involved in English for Academic Purposes.